2013
DOI: 10.4049/jimmunol.1202986
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nucleic Acid–Sensing TLRs in Diverse Autoantibody Specificities and Anti-Nuclear Antibody–Producing B Cells

Abstract: Nucleic acid (NA)–sensing TLRs (NA-TLRs) promote the induction of anti-nuclear Abs in systemic lupus erythematosus. However, the extent to which other nonnuclear pathogenic autoantibody specificities that occur in lupus and independently in other autoimmune diseases depend on NA-TLRs, and which immune cells require NA-TLRs in systemic autoimmunity, remains to be determined. Using Unc93b13d lupus-prone mice that lack NA-TLR signaling, we found that all pathogenic nonnuclear auto-antibody specificities examined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…B cell MyD88 was needed to generate all antinuclear antibodies and a part of rheumatoid factor, whereas the contribution of dendritic cell MyD88 was less relevant. These data are in line with a study using Unc93b1(3d) lupusprone mice that lack signalling of all nucleic acidspecific TLRs in B cells [14]. Interestingly, lupus nephritis entirely depends on B cell MyD88, whereas dendritic cell MyD88 triggers dermatitis [13 As another interesting aspect, targeted TLR7 over-expression in B cells alone is sufficient to specifically trigger RNA autoantibody production followed by aggravated SLE [15].…”
Section: Cell Death and Dead Cell Clearancesupporting
confidence: 75%
“…B cell MyD88 was needed to generate all antinuclear antibodies and a part of rheumatoid factor, whereas the contribution of dendritic cell MyD88 was less relevant. These data are in line with a study using Unc93b1(3d) lupusprone mice that lack signalling of all nucleic acidspecific TLRs in B cells [14]. Interestingly, lupus nephritis entirely depends on B cell MyD88, whereas dendritic cell MyD88 triggers dermatitis [13 As another interesting aspect, targeted TLR7 over-expression in B cells alone is sufficient to specifically trigger RNA autoantibody production followed by aggravated SLE [15].…”
Section: Cell Death and Dead Cell Clearancesupporting
confidence: 75%
“…This model addresses the potential epistatic interaction between TLRs and the lupus associated SLAM family genes in breaking the GC tolerance checkpoint. Recent studies have shown that the deficiency of nucleic acid sensing TLR signaling due to mutations in Unc93b1 is sufficient to interfere with the generation of ANAs (65, 66). Additionally, other pathogenic non-nuclear autoAb specificities including anti-cardiolipin, anti-RBC and anti-MPO, commonly found in SLE patients are also reduced by Unc93b1 mutations (65, 66).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the deficiency of nucleic acid sensing TLR signaling due to mutations in Unc93b1 is sufficient to interfere with the generation of ANAs (65, 66). Additionally, other pathogenic non-nuclear autoAb specificities including anti-cardiolipin, anti-RBC and anti-MPO, commonly found in SLE patients are also reduced by Unc93b1 mutations (65, 66). Our work extends their observation and defines TLR7 as the key nucleic acid sensing TLR for the production of nuclear and non-nuclear antigen specific autoAbs.…”
Section: Discussionmentioning
confidence: 99%
“…The concept is that RNA and DNA–associated autoantigens are bound by the BCR and transported to a TLR-compartment where TLR detection of DNA or RNA provides a second signal promoting B cell activation. Intriguingly, a recent paper demonstrated the surprising finding in UNC-93B deficient lupus-prone mice that the development of non-nuclear autoantibody specificities, including anti-red blood cell and in other contexts anti-MPO, was dependent on TLR signaling in B cells [26]. One possible explanation for the dependence of non-nuclear antibodies on nucleic acid-TLR signaling is that they act as auto-antigens only when associated with nucleic acids, for example on apoptotic cells or neutrophil extracellular traps.…”
Section: The B Cell- Innate Immune System Interfacementioning
confidence: 99%